Platinum Nanoarrays Directly Grown onto a 3D-Carbon Felt Electrode as a Bifunctional Material for Garden Compost Microbial Fuel Cell. Issue 2 (1st February 2021) - Kosimaningrum, Widya Ernayati; Ouis, Mekhaissia; Holade, Yaovi; Buchari, Buchari; Noviandri, Indra; Kameche, Mostefa; Cretin, Marc; Innocent, Christophe
Abstract : The practical implementation of air-breathing microbial fuel cell (MFC) is critically linked to the development of efficient materials as cathode and electrochemically active biofilm-based anode. In this contribution, we demonstrate the feasibility by decorating a 3D carbon felt electrode with Pt nanoarrays (CF@Pt) as a bifunctional electrode material as efficient garden compost bioanode and air-breathing cathode. Half-cell electrochemical characterizations reveal that the onset potential of the anode reaction negatively shifts of about 800 mV to reach −0.4 V vs Ag/AgCl after the growth of the biofilm onto CF@Pt. The investigation before and after the biofilm formation shows that Pt nanoarrays act as excellent electron relays, reducing significantly the charge transfer resistance. For MFC application (with a proton exchange membrane), the use of CF@Pt as bioanode' scaffold and CF@Pt air-cathode enables a drastically enhanced power density of Pmax = 292.3 mW m −2, and a high short-circuit current density jsc = 1.9 A m −2 .